Self-Study of Practice as a Genre of Qualitative Research - Pinnegar, Stefinee. author. aut Link
250 p.
Keywords: Teacher educators live hectic lives at institutional and discipline boundaries. Our greatest potential for influence is through developing relationships with others in our practice. Our work is fundamentally relational and emotional. We are obligated to the teachers we teach and the public students they teach. Our practice exists in the midst of experience, conflicting and often hostile boundaries, and between what we know from research and what we understand from practice. Self-study of practice invites researchers to embrace the hectic and fragmented territory of practice as the space for study. This book educates those who would like to explore practice in the methodology of self-study. It provides both a pragmatic and theoretic guide. It grounds the research in ontology and establishes dialogue as the inquiry process. It supports researchers through the use of frameworks to guide research and explication of strategies for conducting it.